High miR-200a-3p expression has high diagnostic values for hypertensive disorders complicating pregnancy and predicts adverse pregnancy outcomes - Xin He; Danni Ding (BMC, 2022)
Abstract Background Hypertensive disorders complicating pregnancy (HDCP) are various heterogeneous conditions. microRNA (miR)-200a-3p is involved in HDCP diagnosis. This study explored the effects of miR-200a-3p on HDCP patients. Methods A total of 126 singleton HDCP patients including 50 cases of gestation hypertension (GH), 42 cases of mild preeclampsia (MP) and 34 cases of severe preeclampsia (SP), were enrolled as study subjects, and 50 normal pregnant women were selected as the control. Serum miR-200a-3p expression was detected and its efficacy in HDCP diagnosis and grading was evaluated. GH, MP and SP patients were allocated to high/low miR-200a-3p expression groups. The correlation between miR-200a-3p expression and general clinical indexes was analyzed. HDCP patients were allocated to high/low miR-200a-3p expression group and maternal and fetal outcomes were followed up. Effects of miR-200a-3p expression on adverse pregnancy outcome incidence were analyzed. Results miR-200a-3p expression in the serum of HDCP patients was upregulated. The sensitivity and specificity of serum miR-200a-3p level > 1.201 were 87.3% and 96.0%, respectively. Serum miR-200a-3p level in GH, MP and SP patients was increased with the aggravation of the disease. The cut-off value and area under the curve (AUC) of miR-200a-3p for GH, MP and SP diagnosis were 1.145 and 0.9094 (82.0% sensitivity and 88.0% specificity), 1.541 and 0.8126 (73.8% sensitivity and 76.0% specificity), and 1.866 and 0.7367 (64.7% sensitivity and 76.2% specificity), respectively. Serum miR-200a-3p level was correlated with general clinical indexes, fetal birth weight, systolic to diastolic ratio, and fetal growth restriction incidence. High serum miR-200a-3p expression in HDCP patients was associated with increased adverse pregnancy outcomes. Conclusion High miR-200a-3p expression could help to diagnose HDCP, judge severity and was associated with increased adverse pregnancy outcomes.